The effectiveness of a proven chronic disease prevention and screening intervention in diverse and remote primary care settings: an implementation study on the BETTER 2 Program. Issue 3 (2019) - Aubrey-Bassler, Kris; Fernandes, Carolina; Penney, Carla; Cullen, Richard; Meaney, Christopher; Sopcak, Nicolette; Campbell-Scherer, Denise; Moineddin, Rahim; Baxter, Julia; Krueger, Paul; Wilson, Margo; Pike, Andrea; et al.
No abstract available